Basic Research on Tendon Repair: Strategies, Evaluation, and Development - Li, Zhi Jie; Yang, Qian Qian; Zhou, You Lang (Frontiers in Medicine, 2021)
Tendon is fibro-elastic structure that links muscle and bone. Tendon injury can be divided into two types, chronic and acute. Each type of injury and degeneration can cause substantial pain and loss of function. The natural healing process of tendon injury is complex. According to the anatomical position of tendon tissue, the clinical results are different. The wound healing process includes three overlapping stages: wound healing, proliferation and tissue remodeling. Besides, the healing tendon also faces a high re-tear rate. Faced with the above difficulties, management of tendon injuries remains a clinical problem and needs to be solved urgently. In recent years, there are many new directions and advances in tendon healing. This review introduces the tendon injury and sums up the development of tendon healing during recent years, including gene therapy, stem cell therapy, Platelet RICH plasma (PRP) therapy, growth factor and drug therapy and tissue engineering. Although most of these therapies have not yet developed to mature clinical application stage, with the repeated verification by researchers and continuous optimization of curative effect, that day will not be too far away.